2022
DOI: 10.1002/da.23265
|View full text |Cite
|
Sign up to set email alerts
|

How does social support modify the association between psychological distress and risk of suicide death?

Abstract: Background: Social support (SS) has been reported as a factor preventing suicide death, but whether this association is independent of mental status is unclear. The present study examined the effect modification of SS on the association between psychological distress status and risk of suicide death.Methods: Follow-up data for 43,015 subjects participating in a prospective cohort study were analyzed. At baseline, the subjects were asked about SS and mental status with the Kessler six-item Distress (K6) Scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Some research suggested that friends and peers are the most important relationships that provide quality social support (Mahon & Yarcheski, 2017). In accordance with previous studies (Otsuka et al, 2022; Zhao et al, 2022), the multiple regression analysis revealed that social support was engaged in lower suicidal behavior. Second, the current study suggested that psychological strain was predictive of suicidal behavior among university students as existing studies (Zhang et al, 2017; Zhao & Zhang, 2018a) indicated.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Some research suggested that friends and peers are the most important relationships that provide quality social support (Mahon & Yarcheski, 2017). In accordance with previous studies (Otsuka et al, 2022; Zhao et al, 2022), the multiple regression analysis revealed that social support was engaged in lower suicidal behavior. Second, the current study suggested that psychological strain was predictive of suicidal behavior among university students as existing studies (Zhang et al, 2017; Zhao & Zhang, 2018a) indicated.…”
Section: Discussionsupporting
confidence: 91%
“…Taking all these risk factors into account, it is fair to say a variation of 0.01 in suicidal behavior can be attributed to the protective role played by social support. Third, the moderating effect of social support was documented in previous studies that either examined the moderation effect between psychological stress and suicidality (Otsuka et al, 2022) or between opioid misuse and suicide attempts (Agyemang, 2023).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…8 Although some prior studies have also investigated diminished social connections as a determinant of mortality in the context of mental disorders, these findings have been inconclusive and inconsistent. [9][10][11][12][13][14][15] Understanding the interplay of these risk factors could be of importance to identify groups at high risk of premature death, which can inform targeted prevention efforts and help to shed light on the underlying causal factors in the observed life expectancy gap.…”
mentioning
confidence: 99%
“…The majority of prior studies have focused on individuals with depression and are limited by small study populations (<4000 individuals) [9][10][11][12][13][14][15] (for a full overview of previous studies see Supplementary T1 available at https://doi.org/10.1192/bjp.2024.68). To further investigate interaction between mental disorders and diminished social connections on mortality, comprehensive studies based on larger samples are needed.…”
mentioning
confidence: 99%